Direct electricity production from Microalgae Choricystis sp. and investigation of the boron to enhance the electrogenic activity. (3rd April 2020) - Cevik, Emre; Tombuloglu, Huseyin; Anıl, Ismail; Senel, Mehmet; Sabit, Hussein; AbdulAzeez, Sayed; Borgio, J Francis; Barghouthi, Mohammad
Abstract: In this work, a new bio-electrochemical fuel cell was constructed and the effect of boron was investigated to obtain improved electrogenic activity of a green algae ( Choricystis sp. ). In a specially designed bio-electrochemical fuel cell, electrode combinations of indium tin oxide (ITO) and a carbon layer are used. Open circuit potential (OCP) measurements of algal cells placed bio-electrochemical fuel cells were performed with a cyclic on-off illumination of a LED light source. The results revealed that 60 μM is the efficient boron concentration for the algal growth and pigmentation. Higher doses of boron limited the algal growth. However, the algal growth reduced slightly at higher doses, pointing out a possible boron export mechanism in green algae. OCP analysis showed that hydrogen was electro-catalytically reduced at the cathode site and an 18 mV voltage was obtained from boron-deficient (0 μM) Choricystis sp. samples. A significant enhancement in voltage output up to 33 mV was achieved from 60 μM of boron-treated algal samples. The maximum power density was calculated from the boron-treated Choricystis sp. at pseudo-steady state as 42.2 mW m −2 at a current density of 154 mA m −2 . Highlights: The contribution of Boron to enhance the photosynthetic machinery of green algae was investigated. An improved electricity generation was achieved by adding a critical dose of Boron. Green algae Choricystis sp. was isolated and utilized in a bio-electrochemical fuel cell. A significant enhancement in voltage output from 18 to 33 mV by the effect of Boron. Direct electricity production of ~154 mA m −2 with a power density of ~42.2 mW m −2 was obtained.